Teaching DSGE models to undergraduates - Celso José Costa; Alejandro C. Garcia-Cintado (EconomiA, 2018)
This paper puts forward a systematic approach to teaching simple dynamic stochastic general equilibrium (DSGE) models to undergraduates. It proceeds in the following way: first, the structural model of the economy, which includes the households' and firms' problems, is presented and progressively solved. We then find the steady state and log-linearized equations of the model. Next, a productivity shock is simulated on the computer so as to tell a "story" about how the economy behaves. Finally, the model is extended by including the government and the foreign sector. We reckon instructors of macroeconomics will find this path useful in teaching their undergraduate students the basics of DSGE models.
Keywords: A22; E32; 330; Dynamic stochastic general equilibrium (DSGE) modeling; Real Business Cycle model; Undergraduate macroeconomics